Tensioning of tendons force-elongation relationship. (FIP state of the art report., 1986)
Describes the behaviour of tendons as structural elements, and deals with the special problem of the effects of surface condition of the individual tendons. This report is useful to authorities, consultants, contractors, and post-tensioning contractors. It provides information on planning and execution of various types of prestressing work.